Analisis Korelasi Kanonik pada Parameter Kualitas Fisik dan Parameter Kualitas Kimia Air Sungai Ciliwung - Nadya Amelia Dewi Suryana; Itasia Dina Sulvianti; Muhammad Nur Aidi (Department of Statistics, IPB, 2021)
Water is an important factor in fulfilling the needs of living things, therefore the water that is used must be free from bacterias and do not contain any toxic substances. The most common water source comes from the river. Ciliwung River as one of the main rivers used for drinking, household needs, industrial needs, and transportation must have good water quality. Therefore, the Ciliwung River water quality needed to be known. The water quality is measured based on the parameters such as the physical water quality and the chemical water quality. The measurement of those parameters are classified to be complicated as it measured by laboratorium research, so that the identification of the chemical water quality parameter could be done through the physical water quality that is easier and simpler to be measured. This study aims to determine the variable of the physical water parameters that can be used to identify the chemical water quality parameters, so that the water quality of the Ciliwung River can be known in a simpler way. Statistical method that can be used to see the relationship between the two variable groups is the canonical correlation analysis. Canonical correlation analysis is a method in multiple variable analysis used to investigate the relationship of two groups of variables using the linear combination principle of the two variables. Based on the results of the canonical correlation analysis, it can be concluded that there is a relationship between the physical quality of water and the chemical quality of water. The correlation exists between the variables of physical quality of water, which are the water temperature and the content of suspended substances in water, with the variables of chemical quality of water, namely groups of metals (manganese levels in water and iron content in water) and groups of acid (the level of deep phosphate in water, the level of sulfate in water, the level of nitrite in water, and the level of nitrate in water). The relationship between the physical quality of water is positive between the temperature of water and the chemical quality of water whereas negative between the levels of suspended substances in water and the chemical quality of water.